Targeting the Interaction of GABAB Receptors With CHOP After an Ischemic Insult Restores Receptor Expression and Inhibits Progressive Neuronal Death - Bhat, Musadiq A.; Esmaeili, Abolghasem; Neumann, Elena; Balakrishnan, Karthik; Benke, Dietmar (Frontiers in Pharmacology, 2022)
GABAB receptors control neuronal excitability via slow and prolonged inhibition in the central nervous system. One important function of GABAB receptors under physiological condition is to prevent neurons from shifting into an overexcitation state which can lead to excitotoxic death. However, under ischemic conditions, GABAB receptors are downregulated, fostering over-excitation and excitotoxicity. One mechanism downregulating GABAB receptors is mediated via the interaction with the endoplasmic reticulum (ER) stress-induced transcription factor CHOP. In this study, we investigated the hypothesis that preventing the interaction of CHOP with GABAB receptors after an ischemic insult restores normal expression of GABAB receptors and reduces neuronal death. For this, we designed an interfering peptide (R2-Pep) that restored the CHOP-induced downregulation of cell surface GABAB receptors in cultured cortical neurons subjected to oxygen and glucose deprivation (OGD). Administration of R2-Pep after OGD restored normal cell surface expression of GABAB receptors as well as GABAB receptor-mediated inhibition. As a result, R2-Pep reduced enhanced neuronal activity and inhibited progressive neuronal death in OGD stressed cultures. Thus, targeting diseases relevant protein-protein interactions might be a promising strategy for developing highly specific novel therapeutics.